2018
DOI: 10.15547/tjs.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem in adolescents

Abstract: PURPOSE. Self-esteem is an overall evaluation of the person's value, expressed in a positive or negative orientation towards himself. Its development starts from birth and is constantly changing under the influence of experience (1). Especially important is the role of self-esteem in the process of adolescence. During this period, it correlates with both academic achievement and mental health. The aim of this study is to analyze the correlation between academic achievement and self-esteem among teenagers. Fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
19

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 7 publications
2
33
1
19
Order By: Relevance
“…This might be because adolescent boys and girls are getting equal opportunities in recent years. This finding is in contrast with a Pakistani and Bulgarian study where boys showed higher self-esteem level than girls [ 41 , 42 ]. Another Nepali study conducted among nursing students showed that low self-esteem was due to stress in the academic environment [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This might be because adolescent boys and girls are getting equal opportunities in recent years. This finding is in contrast with a Pakistani and Bulgarian study where boys showed higher self-esteem level than girls [ 41 , 42 ]. Another Nepali study conducted among nursing students showed that low self-esteem was due to stress in the academic environment [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Adolescenti tak vo veľkej miere finalizujú dôležitú vývinovú úlohu -formovanie selfkonceptu, ktorého súčasťou je aj sebaobraz, sebahodnota a vlastná identita (Kusý, 2017). Sebahodnotenie teda v tomto období zohráva pre mladého človeka veľmi dôležitú úlohu (Minev, Petrova, Mineva, Petkova, & Strebkova, 2018). Obdobie adolescencie je taktiež citlivým pre vytváranie si vzťahu k hodnotám.…”
Section: úVodunclassified
“…Elliot& Church, 2003, Martin, et al, 2003 (Urdan, 2004, Leondari& Gonida, 2007, Thomas& Gadbois, 2007, Chang, 2010, Gadbois & Sturgeon, 2011 (Adil, et al, 2020, 58 (Schwinger & Stiensmeier-Pelster, 2011, Park & Brown, 2014, Yavuzer, 2015, Ferradás, et al, 2016b, Ferradás, et al, 2018 (Lane, et al, 2004, Imran, 2013, Preeti, et al, 2016, Jagtap, 2018, Christy& Mythili, 2020 . ‫دة‬ ‫د‬ ‫ثس‬ ‫ر‬ ‫ئت‬ ‫د‬ ‫د‬ ‫نت‬ ‫د‬ ‫د‬ ‫د‬ ‫د‬ ‫ف‬ ‫ثخت‬ ‫د‬ ‫د‬ ‫،نه‬ ‫ال‬ (Minev, et al, 2018 (Ferradás, et al, 2017) . ‫ع‬ ‫كت‬ ‫تهص‬ ‫ئ‬ ‫نت‬ ‫ثسة‬ ‫ر‬ ‫ت‬ (Ferradás, et al, 2018 (Ferradás, et al, 2016a, Ferradás, et al, (Ross, et al, 2002, Bobo, et al, 2013 (Ross, et al, 2002, Bobo, et al, 2013, Nosenko, et al, 2016 gender differences in self-handicapping.…”
Section: ‫دل‬ ‫وق‬mentioning
confidence: 99%